Hydraulic pressure can't harm rod clipper control system - SUN YIJIANG (2016)
The utility model relates to a hydraulic pressure can't harm rod clipper control system, including feeding mechanism, be used for supplementary pay -off clamping mechanism, block the mechanism and be used for the supplementary locking mechanism who shears the rod, still include oil circuit control system and electric control system. Adopt the technical scheme of the utility model afterwards, through oil circuit control system as feeding mechanism, clamping mechanism, the power resources of blocking the action of mechanism and locking mechanism, orderly cooperation and linking of each action are realized through electric control system for accomplish the cycle that rod blocked and shortened, improved the work efficiency of clipper, reach reduce cost's effect on the whole. Set up in oil circuit control system that the accumulator is used for collecting unnecessary pressure and the flow provides the energy requirement for locking mechanism, clamping mechanism and feeding mechanism etc. Realized power and energy's the biggest utilization, reduced enterprise's power cost in process of production.